2023
DOI: 10.1097/mnh.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease with unknown cause across the global spectrum

Abstract: Purpose of reviewIn the 1990s, a type of chronic kidney disease with unknown cause (CKDu) was identified in Central America and Sri Lanka. Patients lacked hypertension, diabetes, glomerulonephritis, or other usual causes of kidney failure. Affected patients are predominantly male agricultural workers aged 20--60 years, living in economically disadvantaged areas with poor access to medical care. Patients typically present late and progress to end-stage kidney disease within 5 years, resulting in social and econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In other studies, the relationship between hypohydration status and degraded mood was consistent. The findings showed that low water intake or low 24 h urine volume is associated with negative health outcomes, including an increased risk of chronic kidney disease, the development of kidney stones, and altered glucose homeostasis [ 33 , 34 ]. In additional studies, measurements of self-reported changes in mental state consistently found associations between dehydration and mood in conjunction with changes in performance.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the relationship between hypohydration status and degraded mood was consistent. The findings showed that low water intake or low 24 h urine volume is associated with negative health outcomes, including an increased risk of chronic kidney disease, the development of kidney stones, and altered glucose homeostasis [ 33 , 34 ]. In additional studies, measurements of self-reported changes in mental state consistently found associations between dehydration and mood in conjunction with changes in performance.…”
Section: Discussionmentioning
confidence: 99%